Correlation between Personnel Knowledge and Suitability of Intravenous Admixture Preparations at PKU Muhammadiyah Wonosari Hospital - Madury, Shalahuddin Al; Wiedyaningsih, Chairun; Sugiyono, Sugiyono; Mutiara, Rina (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Background: Knowledge and skills related to the preparation and administration of sterile preparations, including the principles of technique aseptic according to procedures, are very important for personnel is compounding intravenous admixture. This knowledge is essential to avoid medication errors and increase patient safety. Improper preparation or administration of intravenous medications can result in patient injury or even death due to medication errors.Objectives: The purpose of this study is to examine the correlation between the appropriateness of antibiotic intravenous admixture preparations and the degree of personal knowledge.Methods: This research was conducted in an observational manner with a cross-sectional design and quantitative analysis. A total of 33 respondents who were in charge of intravenous admixture preparations at PKU Muhammadiyah Wonosari Hospital were measured for their level of knowledge and tested for their relationship with the suitability iv admixture process in the October-November 2022 period and analyzed statistically with the contingency coefficient correlation test.Results: The results of this study showed a p-value of 0.001 indicating a significant correlation between the level of knowledge and suitability for the preparation stage. A p-value of 0.012 indicated a correlation between the level of knowledge and modification of the intravenous injection preparation mixing procedure. Personal profession and training have an effect on the mixing of intravenous injection preparations with a p-value of 0.021; and 0.027.Conclusion: Increased knowledge and continuous training can be implemented to improve the quality of intravenous admixture produced by personnel.